Physiological mechanisms of muscle strength and power are dependent on the years post obtaining peak height velocity in elite juniors rowers: A cross-sectional study - de Almeida-Neto, P. F.; de Morais Ferreira, A. B.; Baxter-Jones, A.; de Medeiros, J. A.; Felipe da Silva, L.; Silva Dantas, P. M.; de Araújo Tinoco Cabral, B. G. (PLOS ONE, 2023)
Background: It is not yet known whether the years after peak height velocity (PHV) are associated with the physiological mechanisms of muscle strength and power in Juniors rowers.